Local meanings of international student assessments: an analysis of media discourses of PISA in China, 2010-2016. Issue 3 (3rd April 2022) - Hu, Zi
ABSTRACT: The Programme for International Student Assessment (PISA) has garnered increasing attention since its inception in 2000. Correspondingly, there has been heightened interest in 'PISA poster countries' like Singapore and Shanghai-China. Yet to date, little is known about the processes and dynamics of the construction of PISA discourses within these 'poster countries'. This paper examines the Chinese print media's reception and interpretation of PISA. Using content analysis of media reportage in 2010, 2013 and 2016, the paper identifies core patterns and themes within the media-generated PISA discourses in China and traces changes in the media discourses over time. The findings shed light on a 'mediatisation' process where the Chinese media's interpretation of PISA gets shaped by culture-specific factors such as dominant political ideology, national aspirations, and histories. As such, PISA has acquired localised meanings in China and serves as an instrument to promote national development agenda and justify education reforms.